NMR study of seven coumarins from Mammea siamensis - Vilailak Prachyawarakorn (2018)
Seven known mammea coumarins, mammea A/AA cyclo D (1), mammea A/AD cyclo D (2), mammea A/AB cyclo D (3), mammea A/AC cyclo F (4), mammea A/AB cyclo F (5), mammea A/AA cyclo F (6), mammea B/AC cyclo F (7), were isolated for the first time from the hexane extract of Mammea siamensis. A detailed analysis of both ID and 2D NMR spectral data of these compounds was made. © Swets & Zeitlinger.